Fourier-transform infrared spectrometry determination of the metabolic changes during a maximal 400-meter swimming test - Petibois, C.; Deleris, G. (International Journal of Sports Medicine, 2003)
We describe the metabolic changes in the blood that appeared during a maximal 400-m swimming test in 7 male swimmers by Fourier-transform infrared spectrometry (FT-IR spectrometry). A 400-m test (255.9 +/- 6.8 s) was performed during which stroke frequency and time to complete each pool distance were recorded. In three other tests, the first 100 m, 200 m, and 300 m were swam at the same stroke frequency and velocity. Capillary blood samples were taken at rest and after tests to analyze change in plasma contents by FT-IR spectrometry. Best swimmers were characterized by higher glycemia increase at the onset of exercise (r = -0.91; p < 0.01). Lactate increase was also higher after 300 m (r = -0.97; p < 0.01). Higher amounts of fatty acids were also available at the end of exercise, as assessed by the relationships found between swimming velocity and concentrations of albumin (r = 0.96; p < 0.01), apolipoprotein C 3 (r = 0.93; p < 0.01), triglycerides (r = -0.81; p < 0.05), and fatty acids (r = 0.97; p < 0.01). This metabolic response allowed the best swimmers to maintain longer their initial swimming velocity. The best swimmers presented also higher amino-acid concentration increase during exercise (r = 0.91; p < 0.01). Therefore, performance competence originated probably from better regulation in carbohydrate, lipid, and amino-acid metabolism.